Timeliness of primary childhood vaccination in a rural area of Puducherry, South India: evidence from routine management information system - Ramaswamy, Gomathi; Pruthu, T. K.; Selvaraj, Kalaiselvi; Vinayagamurthy, V. M.; Chinnakali, Palanivel (International Journal of Contemporary Pediatrics, 2017)
Background: Immunization plays an important role in reducing mortality due to vaccine preventable diseases in children. In areas with high vaccine coverage, age-appropriate vaccination or timeliness of vaccination will be helpful in assessing quality of vaccination program. The objective was to assess the delay in primary childhood vaccination in a primary health center (PHC) of rural Puducherry. Methods: A record based study was conducted in a primary health center situated in rural Puducherry using data from immunization and antenatal records. Children born between 1st January 2009 and 30th November 2013 were included in the study. Delay in vaccination of diphtheria-tetanus-pertussis 1 (DPT1), DPT2, DPT3 and measles were studied. Results: A total of 457 children were included, 52.5% were males, and 47.5% were females. Immunization coverage was 100% for all vaccines. Delay in vaccination more than 2 weeks from the due date of vaccination for DPT1, DPT2, DPT3 and measles were 7.4%, 41.9%, 64.4% and 38.8% respectively. Median (interquartile range) days of delay for DPT1, DPT2, DPT3 and measles was found to be 6 (4-8), 13 (7-20), 19 (12-30) and 11 (4-24) respectively. Children with higher birth order were vaccinated with significant delay for DPT3 (p = 0.008). Delay in vaccination was less in children from the village where PHC is located (p < 0.001). Conclusion: Vaccination coverage for DPT and measles is high. There are delays in vaccination for DPT and measles, though not so high, there is scope for improving timeliness of vaccination in this rural area.